Articulations of Inequality in Educational Psychology Practice - Kirkegaard Jensen, Sarah; Szulevicz, Thomas (International Review of Theoretical Psychologies, 2026)
This article delves into the historical and theoretical dimensions of inequality within educational psychology (EP) practice. From its inception, EP practice has implicitly addressed inequality, initially focusing on malnutrition and poverty, which later transformed into concerns about innate and inherited IQ. The article identifies two dominant articulations of inequality in EP practice: clinical assessment and social justice. These articulations, while intertwined, highlight the evolving understanding and practices around inequality within the field. It is argued that the clinical-assessment articulation of inequality overlooks structural and social components of inequality in favor of individualized understandings. The social justice articulation emphasizes identity and representational issues related to inequality. However, our claim is, that this approach paradoxically also risks individualizing issues of inequality, thus across both articulations, inequality often becomes a methodological concern, either for developing evidence-based practices or for individual action by educational psychologists. This focus risks detaching inequality from its social and historical contexts. The article argues for theoretical development and engagement to highlight the normative, historical situatedness of EP practice and to address the risk of detaching inequality from its social and historical conditions.